Aerosol Concentrations in Relationship to Local Atmospheric Conditions on James Ross Island, Antarctica - Kavan, Jan; Dagsson-Waldhauserova, Pavla; Renard, Jean Baptiste; Láska, Kamil; Ambrožová, Klára (Frontiers in Earth Science, 2018)
Several important ice-free areas (e.g. Seymour Island, Cape Lamb on Vega Island, Terrapin Hill) are located in the region of Eastern Antarctic Peninsula. The largest deglaciated region can be found on the Ulu Peninsula, James Ross Island, where the study was carried out. This area of 312 km2 has been found important active High Latitude Dust source. Aerosol concentrations and local wind properties are described together with their linkages and typical synoptic situations. The highest aerosol concentrations of 57 µgm−3 for PM10 were detected during the high wind speed events exceeding 10 m s-1, which is also a threshold level for activating local mineral material sources. Apart the local dust sources, influence of long range aerosol transport out of Antarctica (especially Patagonia) is discussed too.